PENYIMPANGAN NILAI AGAMA ISLAM DALAM NOVEL ORANG-ORANG BLANTI KARYA WISRAN HADI - Oktaria, Lely; bahardur, Iswadi; Hartati, Yulia Sri (Pendidikan Bahasa Indonesia, 2014)
This research the purpose of this research to describe Islam valueâs deviation in Orang-orang BlantiâsÂ novel work by Wisran Hadi. The Islam value relate with: (1) Islam valueâs deviation which interrelated whit moralÂ in novel of Orang-orang Blanti that a by work Wisran Hadi, (2) Islam valueâs deviation which interrelatet whit fait in novel Orang-orang Blanti that a work by Wisran Hadi, (3) Islam valueâs deviation which interrelatet whit Islam law in novel Orang-orang Blanti that a work by Wisran Hadi. The type of this research is qualitative research. Medhod base of research analysis is found Islam valueâs deviation is based on moral, faith, Islam law.